Tuning the electrical and optical anisotropy of a monolayer black phosphorus magnetic superlattice. (1st March 2018) - Li, X J; Yu, J H; Luo, K; Wu, Z H; Yang, W
Abstract: We investigate theoretically the effects of modulated periodic perpendicular magnetic fields on the electronic states and optical absorption spectrum in monolayer black phosphorus (phosphorene). We demonstrate that different phosphorene magnetic superlattice (PMS) orientations can give rise to distinct energy spectra, i.e. tuning the intrinsic electronic anisotropy. Rashba spin–orbit coupling (RSOC) develops a spin-splitting energy dispersion in this phosphorene magnetic superlattice. Anisotropic momentum-dependent carrier distributions along/perpendicular to the magnetic strips are demonstrated. The manipulations of these exotic electronic properties by tuning superlattice geometry, magnetic field and the RSOC term are addressed systematically. Accordingly, we find bright-to-dark transitions in the ground-state electron–hole pair transition rate spectrum and the PMS orientation-dependent anisotropic optical absorption spectrum. This feature offers us a practical way of modulating the electronic anisotropy in phosphorene by magnetic superlattice configurations and detecting this modulation capability by using an optical technique.